Mitochondrial Cardiomyopathy Presenting as Dilated Phase of Hypertrophic Cardiomyopathy Diagnosed with Histological and Genetic Analyses - Toshiki Kuno; Syohei Imaeda; Yohei Asakawa; Hiroshi Nakamura; Genzou Takemura; Daisuke Asahara; Akira Kanamori; Tomoyuki Kabutoya; Yohei Numasawa (Case Reports in Cardiology)
We report a case with 46-year-old man diagnosed with mitochondrial cardiomyopathy in the dilated phase of hypertrophic cardiomyopathy. Since cardiac magnetic resonance imaging, beta-methyl-p-I123-iodophenyl-pentadecanoic myocardial scintigraphy, and positron emission tomography/computed tomography revealed no remarkable findings, we performed electron microscopic examination, which aided in diagnosing mitochondrial cardiomyopathy. Muscle biopsy was also compatible with mitochondrial encephalomyopathy, lactic acidosis, and stroke-like episodes and DNA analysis also concluded it. Since muscle biopsy is less invasive for patients compared to endomyocardial biopsy, cardiologists need to consider it. The diagnosis of mitochondrial cardiomyopathy is helpful because it is a genetic condition and also for consideration of device therapy, as well as management for acute crisis.